Exploration of the relationship between word-association and learners’ lexical development with a focus on American L1 and Croatian L2 speakers - Séguin Maja (ExELL (Explorations in English Language and Linguistics))
Vocabulary acquisition is a dynamic process and there is a constant change in the way words are stored in the mental lexicon. Word association tests are used in linguistic research to observe to which extent mental mapping can be understood. This paper presents the results of a word association game consisting of seven words administered to second language speakers, and native speakers for comparative purposes. The results indicate the possibility of a link between experiences and associations, which leads to the recommendation for teachers to create activities and new experiences that demand the learner’s personal involvement in expanding their vocabulary.